The Real Interest Rate Differential : International Evidence Based On Non-Linear Unit Root Tests - Ahmad Zubaidi, Baharumshah; Liew Venus, Khim Sen; Chan, Tze Haw (Blackwell Publishing Ltd, 2009)
This paper aims at testing international parity conditions by using non-linear unit root tests advocated by Kapetanios et al. (2003, KSS). Results from the KSS tests based on 17 countries (G7 and 10 Asian countries) overwhelmingly show that the adjustment of real interest rates towards real interest rate parity (RIP) follows a non-linear process except for the Taiwan, Hong Kong and Philippines relationships with both the USA and Japan. Overall, the empirical results are in favour of RIP using the USA and Japan as the centre countries but only if non-linearities are accounted for in the data-generating process. Our findings confirm that interest rate differentials, like the real exchange rates reported in recent literature, display a non-linear mean reversion process.